PROCESS OF TECHNOLOGY TRANSFER AS MAIN PROBLEM OF NANOTECHNOLOGY COMMERCIALISATION - A. V. Lovtakov (Модернизация, инновация, развитие)
The article presents main problems of commercialization of nanotechnology. Moreover article highlights the process of technology transfer and its’ role in nanotechnology commercialization.